Enantioselective modification of sulfonamides and sulfonamide-containing drugs via carbene organic catalysis - Song, Runjiang (2021)
A carbene-catalyzed method for highly enantioselective modification of sulfonamides is disclosed. The reaction proceeds under mild conditions with broad substrate scope, wide functional group tolerance, and good to excellent yields. When multiple sulfonamides or amines are present in the same molecule, the reaction occurs in a highly chemo-selective manner. Application of our method allows for selective modification of sulfonamide-containing drug molecules to form the corresponding phthalidyl derivatives as potential prodrugs. Experimental observations and DFT calculations suggest that the reaction proceeds via a stepwise addition pathway, assisted by Li+ ions or protons. Non-covalent interactions, such as cation–π interactions, play important roles in enhancing the reactivity and controlling the enantioselectivity of the reaction.